Goal-Directed Mobility of Medical Inpatients–A Mini Review of the Literature - Heinzmann, Jeannelle; Baumgartner, Christine; Liechti, Fabian D. (Frontiers in Medicine, 2022)
Background: Inpatients spend most of their hospitalization in bed, which can lead to negative physical, social, and psychological outcomes, especially in the geriatric population. Goal-directed mobilization involves setting mobility goals with patients and care teams working to-gether towards achieving these goals. Methods: Three different platforms (SCOPUS, Ovid Medline, PubMed) were searched. Search terms included "goal-directed", "goal-attainment" or "goal-setting", and "inpatient" or "hospitalization" and "mobility" or "mobilization". Articles were included if mobility goals were set in acutely hospitalized adults. Studies were excluded if only covering specific illness or surgery. Results: 173 articles were screened for inclusion by two independent reviewers. In the final analysis, thirteen articles (5 randomized controlled trials, 2 post-hoc analyses, 3 quality-improvement projects, 1 pre-post two group analysis, 1 comment and 1 study protocol) were assessed. Goal-directed mobilization improved mobility-related outcomes, i.e., level of mobili-zation, activity, daily walking time and functional independence. Readmissions, quality of life, discharge disposition and muscle weakness were not significantly altered and there was con-flicting evidence regarding length of stay and activities of daily living. Conclusion: There is a lack of evidence of goal-directed mobilization on relevant outcomes due to the low number of studies in the field and the study design used. Further research on goal-directed mobility should use standardized mobility protocols and measurements to as-sess mobility and the effects of goal-directed mobility more accurately and include broader patient populations.